Johnny Cash the life - Hilburn, Robert (New York Little, Brown and Company, 2013)
A noted music critic who knew him tells the unvarnished truth about Cash, whose personal life was far more troubled and his artistry much more profound than even his most devoted fans have realized.
Dyess and the dream -- Vivian and the Air Force -- Memphis and Sam Phillips -- Sun records, the Tennessee two, and Boom Chicka Boom -- "Hey, Porter," "Folsom Prison Blues," and a baby girl -- Louisiana hayride and "I Walk the Line" -- Columbia records, "Big River," and pills -- Hollywood, Town hall party, and Lorrie Collins -- "Ride This Train" and the Huntsville prison rodeo -- Billie Jean and the marriage proposal -- Casitas springs and Saul Holiff -- June Carter -- The drugs and Carnegie Hall -- "Ring of Fire," "Understand Your Man," and the troops in the far East -- Newport, Bob Dylan, "Ira Hayes," and Ballads of the True West -- The Los Padres fire and the El Paso drug bust -- The deathwatch -- The divorce, Bob Johnston, and a suicide tale -- Folsom prison and marrying June -- The Johnny Cash show and superstardom -- Kris Kristofferson, Billy Graham, and Anita Carter -- "It's a Boy" and the White House -- Israel and the calling -- The Gospel Road and a change of managers -- Family man and national icon -- Losing the muse -- The pills return and all hell breaks loose -- No one's listening -- At Betty Ford and dropped by Columbia records -- The beginning of the Mercury era and heart surgery -- Branson, the rock and roll hall of fame, and U2 -- Rick Rubin -- The end of the concert trail and struggling with physical pain -- A hero again -- "The Man Comes Around" and "Hurt" -- The final days.
Includes bibliographical references (pages 646-663), discography (pages 639-644) , filmography (pages 644-645) and index.
110831
Keywords: Cash, Johnny -- 1932-2003; Country musicians -- United States -- Biography; Biography & Autobiography -- Composers & Musicians; United States; collective biographies; Biographies